Managing the academic unit / Allan Bolton. - Bolton, Allan (Managing universities and colleges : guides to good practice, 2000)
Managing the Academic Unit gives guidance on key departmental concerns such as resource allocation, personnel, marketing, student recruitment, facilities and quality. It also examines the qualities required of directors, deans, and heads of dept.